Baby Ruby [videorecording (DVD)] - Merlant, Noémie, 1988-; Harington, Kit, 1986-; Hagner, Meredith, 1987-; Birney, Reed, 1954- (Magnolia Home Entertainment, 2023)
It tells the story of Jo, a lifestyle entrepreneur who is happily pregnant and awaiting the arrival of her first child. But soon after she and her husband welcome their new baby girl Ruby home, something starts to feel off. Jo soon finds herself plunged into a waking fever dream where everyone's motives seem sinister including Ruby's.